1979
DOI: 10.1001/archderm.115.9.1074
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy for psoriasis. Psoralens plus long-wave ultraviolet radiation with betamethasone valerate

Abstract: In the treatment of psoriatic patients with psoralens plus long-wave ultraviolet radiation (PUVA), clearing of psoriatic lesions was obtained more quickly and with smaller doses of ultraviolet light when topically applied corticosteroid therapy was added. Twelve patients with symmetrical plaque-type psoriasis were given PUVA on one side of the body and PUVA plus betamethasone valerate on the other side in a paired comparison study. Ten of the patients had faster clearing of lesions on the side that was treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…These were combination therapy studies with conflicting results in which one arm each investigated PUVA with placebo. From the other studies, 17 studies were assigned a grade of evidence of B 114,239–253 and one a grade of evidence of C 254 . This results in a level of evidence of 2.…”
mentioning
confidence: 99%
“…These were combination therapy studies with conflicting results in which one arm each investigated PUVA with placebo. From the other studies, 17 studies were assigned a grade of evidence of B 114,239–253 and one a grade of evidence of C 254 . This results in a level of evidence of 2.…”
mentioning
confidence: 99%
“…Combined therapies appear to be the most effective of all in clearing recalcitrant widespread and severe psoriasis [1]. One of the most frequent of the combination is PUVA topical steroid [8]. In contrast with PUVA, topical steroids appear to show a more rapid rate of clearing and a smaller total UVA dose when used in combination [9].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, another study on the combination of betamethasone with oral PUVA showed a synergistic effect. In all treated patients, skin lesions healed after an average of 13.6 days compared with an average of 20.25 days in the oral PUVA group [221] (EG B).…”
Section: Phototherapymentioning
confidence: 99%